Studi Deskriptif Penerapan Screen Time terhadap Aspek Perkembangan Anak Usia Dini - Nurhamida; Masnipal Marhun; Dinar Nur Inten (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Screen time is a term used to describe the amount of time individuals spend interacting with televisions, computers, laptops, smartphones, and video games. Giving screen time to early childhood is a necessity in entering the industrial era 4.0 which can change perspectives and lifestyles. The aim of this research is to analyze the planning, implementation, and assessment of screen time on children's development in early childhood education institutions. This research uses a qualitative approach with descriptive methods. Data collection techniques using observation, interviews, and documentation. The research subjects were teachers and parents of students. Data analysis follows the procedures of data collection, data reduction, data presentation, conclusion, and data verification. The results of the study show that the application of screen time in early childhood education institutions is related to all child development tasks. Effective application of screen time can support learning and enhance children's learning and playing experiences, strengthening communication links between children, parents, and others. The research has implications for improving teacher skills in implementing screen time in early childhood education institutions. Abstrak. Screen time merupakan istilah digunakan untuk menjelaskan jumlah waktu yang dihabiskan individu untuk berinteraksi dengan televisi, komputer, laptop, smartphone, hingga video games. Pemberian screen time pada anak usia dini menjadi kebutuhan memasuki era industri 4.0 yang dapat merubah cara pandang dan pola hidup. Penelitian bertujuan menganalisis perencanaan, penerapan, dan penilaian pemberian screen time terhadap perkembangan anak di lembaga PAUD. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Subjek penelitian adalah guru dan orang tua siswa. Analisis data mengikuti prosedur pengumpulan data, reduksi data, penyajian data, kesimpulan, dan verifikasi data. Hasil penelitian menunjukkan penerapan screen time di lembaga PAUD berkaitan dengan seluruh tugas perkembangan anak. Penerapan screen time yang efektif dapat mendukung pembelajaran dan meningkatkan pengalaman belajar dan bermain anak, memperkuat hubungan komunikasi antara anak, orang tua, dan orang lain. Penelitian berimplikasi bagi peningkatan keterampilan guru dalam menerapkan screen time di lembaga PAUD.